Spatial and temporal patterns of mass bleaching of corals in the Anthropocene - Hughes, T.; Anderson, K.; Connolly, S.; Heron, S.; Kerry, J.; Lough, J.; Baird, A.; Baum, J.; Berumen, M.; Bridge, T.; Claar, D.; Eakin, C.; et al. (The American Association for the Advancement of Science, 2018)
Tropical reef systems are transitioning to a new era in which the interval between recurrent bouts of coral bleaching is too short for a full recovery of mature assemblages. We analyzed bleaching records at 100 globally distributed reef locations from 1980 to 2016. The median return time between pairs of severe bleaching events has diminished steadily since 1980 and is now only 6 years. As global warming has progressed, tropical sea surface temperatures are warmer now during current La Niña conditions than they were during El Niño events three decades ago. Consequently, as we transition to the Anthropocene, coral bleaching is occurring more frequently in all El Niño-Southern Oscillation phases, increasing the likelihood of annual bleaching in the coming decades.